Development and testing of the media monitoring tool MedISys for early identification and reporting of existing and emerging plant health threats1. (25th June 2015) - Alomar, O.; Batlle, A.; Brunetti, J.M.; García, R.; Gil, R.; Granollers, A.; Jiménez, S.; Laviña, A.; Linge, J. P.; Pautasso, M.; Reverté, C.; Riudavets, J.; et al.
Abstract : Media monitoring for emerging risks has become an essential tool in public health. This approach also has the potential to deliver early warning of emerging risks to plant health. The European Food Safety Authority (EFSA) has launched a project in collaboration with the Joint Research Centre (JRC) of the European Commission to make use of the Medical Information System (MedISys) media monitoring tool for monitoring plant health threats. This paper provides a summary of the project, which is taking place in partnership with the University of Lleida and the Institut de Recerca I Tecnologia Agroalimentàries. The four specific objectives of the project are: (1) to collate new and appropriate media and information sources, (2) to develop a multilingual ontology for the global identification of emerging new plant health threats, (3) to develop strategies to monitor (re‐)emerging plant health threats at global and regional scales, and (4) to test approaches for reporting the identified warnings to the relevant EFSA units and experts through the MedISys interface, including mapping and georeferencing. The plan and structure of the project are presented with examples of preliminary results.